Tata Kelola Pemerintahan dalam Hukum Islam - Nur Paikah (Al-Bayyinah, 2019)
Abstract:This study is a conceptual review of governance management in the perspective of Islamic law. It focuses on the management of a state by reviewing the literature relevant to the system of state governance in Islam. The researcher applied a normative and historical approach using analysis of the concept proposed by Islamic scholars in relation to the system of governance in Islam. The result of the study indicates that the system of government practiced by the Prophet Muhammad and Khulafaurrasidin became a role model in the management of a state. Islamic law has given the concept of state administration professionally and equitably. The Islamic government must be able to provide a concept of religion and at the same time provide the best security and services for its people. Keywords: Governance-Management-Islamic Law.